Pengembangan Aplikasi Mobile Sistem Informasi Pengaduan Masyarakat dengan Pendekatan Waterfall dan Pengujian Black Box - Dita Sucinta Sembiring; Muhammad Dedi Irawan; Yustria Handika Siregar (Ali Institute of Research and Publication, 2024)
Indonesia, as a country that adheres to democracy, always strives to exercise supreme power in the hands of the people. One form of people's political participation in a democratic government is the participation of community members in general elections. Public complaint applications are really needed in an agency to find out the success of work, correct deficiencies and receive suggestions for tasks that have been carried out. The research method used in this research is a qualitative method, where research implementation procedures are flexible according to needs, as well as situations and conditions in the field. The application of technology, especially the public complaint information system, will make devices easier by reducing limitations in providing services to the public so that it can help the public to obtain and convey information in a short time, wherever they are. which in this research uses a waterfall approach for system design, tested using the black box testing method which proves that the system runs well.